2021
DOI: 10.1093/fpa/orab033
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with Public Opinion at the Micro-Level: Citizen Dialogue and Participation in German Foreign Policy

Abstract: This article analyzes how and why foreign policy (FP)-makers use dialogue and participation processes (DPPs) with (groups of) individual citizens as a source of public opinion. Taking Germany as a case study and drawing on DPP initiatives by the Federal Foreign Office (Auswärtiges Amt, AA) since 2014, we analyze the officials’ motivation for establishing such processes and find four different sets of motivation: (1) image campaigning, (2) educating citizens, (3) listening to citizens, and (4) changing the citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
1
0
2
Order By: Relevance
“…Based on this algorithm, an intelligent prediction platform is constructed to predict the fluctuation of data more accurately. The literature [14] analyzes the motivation for the establishment of an opinion statistics program in Germany and provides a framework for decision-making based on the analysis of the importance of officials dealing with public opinion at the micro level, which fills a gap in the research in the field of decision analysis. It is shown that the purpose of public relations is secondary to image promotion, educating citizens, inviting citizens, and changing citizens' decisions in democratic decision-making that accompanies time are the main motives for establishing such procedures in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this algorithm, an intelligent prediction platform is constructed to predict the fluctuation of data more accurately. The literature [14] analyzes the motivation for the establishment of an opinion statistics program in Germany and provides a framework for decision-making based on the analysis of the importance of officials dealing with public opinion at the micro level, which fills a gap in the research in the field of decision analysis. It is shown that the purpose of public relations is secondary to image promotion, educating citizens, inviting citizens, and changing citizens' decisions in democratic decision-making that accompanies time are the main motives for establishing such procedures in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Deitelhoff 2012, S. 69-77). Auf die deutsche ASP trifft ein gestiegener Legitimationsbedarf in unterschiedlichen Hinsichten grundsätzlich zu, und zwar bereits vor der deklarierten "Zeitenwende" (Opitz et al 2022). Dialog mit und die Beteiligung von Bürger*innen wäre dann also als Teil einer Strategie zu verstehen, durch die Eliten versuchen, eine allmähliche Anpassung der Außen-und Sicherheitspolitik zu legitimieren.…”
unclassified
“…Sowohl aus empirischer als auch theoretischer Sicht greift ein solches Verständnis des Verhältnisses zwischen Politisierung und (Selbst-)Legitimation jedoch zu kurz. In Hinblick auf den vorliegenden Fall haben wir innerhalb des AA unterschiedliche Beweggründe identifiziert, die die Initiierung und Fortführung von Formaten der außen-und sicherheitspolitischen Bürgerbeteiligung vor 2022 motivierten (Opitz et al 2022). Manche Diplomat*innen verstanden die Dialoge in der Tat als Teil einer Imagekampagne.…”
unclassified